Clinical relevance of alpha-fetoprotein in determining resection margin for hepatocellular carcinoma. Issue 11 (March 2019) - Lee, Jin-Chiao; Cheng, Chih-Hsien; Wang, Yu-Chao; Wu, Tsung-Han; Lee, Chen-Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Chan, Kun-Ming; Lee, Wei-Chen
Abstract : Abstract: Liver resection for hepatocellular carcinoma (HCC) is associated with high recurrence rates. Adequate resection margin which is carried out by surgeons may reduce tumor recurrence. Nevertheless, the margin width remains controversial particularly in cirrhotic patients where optimal parenchymal preservation is necessary. This study aims to find a reference for proposing the resection margin when liver resection is planning. Totally, 534 patients who received liver resection for HCC were included. The clinical profiles of the patients, tumor characteristics and patients' survival were all collected. The patients were classified according to resection margin (<0.5 cm, 0.5–0.99 cm, and ≥1 cm) and preoperative α-fetoprotein (AFP) levels (<15 ng/ml, 15–200 ng/ml, and >200 ng/ml), then survival was calculated. Most of the patients had hepatitis B (52.4%) and hepatitis C (24.0%) infection. Multivariate analysis showed that narrow resection margin (<0.5 cm) (hazard ratio [HR]: 1.323, P  = .024), high AFP level (≥15 ng/ml) (HR: 1.305, P  = .039), major extent of resection (≥3 segments) (HR: 1.507, P  = .034), and underlying cirrhosis (HR: 1.404, P  = .009) were independent risk factors for disease-free survival. In further survival analysis, resection margin was not significant for disease-free survival if serum AFP levels were <15ng/ml. However, for the patients with AFP level between 15 and 200 ng/ml, resection margin ≥0.5 cm was significant to improve 5-year disease-free survival from 24.6 months to 38.7 months ( P  = .040). For the patients with AFP >200 ng/ml, resection margin had to be extended to ≥1 cm to improve 5-year disease-free survival from 33.9 months to 48.8 months ( P  = .012). When the patients meeting AFP <15 ng/ml with tumor-free margin, AFP between 15 and 200 ng/ml with margin ≥0.5 cm, and AFP level >200 ng/ml with margin ≥1 cm were compared, their survival rates were not different. Adequate resection margin can be guided by pre-operative AFP levels. Tumor-free margin is enough for patients with normal AFP level. A resection margin ≥0.5 cm is advised for the patients with AFP between 15 and 200 ng/ml, and ≥1 cm for the patients with AFP over 200 ng/ml.